Evaluación regional de la roca reservorio en el cretácico superior y paleoceno mediante la caracterización petrofísica y modelamiento de física de rocas al suroeste de la Cuenca de Santos, Brasil (2020)
In the oil industry is essential to perform an adequate reservoir characterization that integrates studies that include an analysis of the Petrophysics properties, the physical and geological mechanisms that determine the elastic parameters of the reservoir which allow to obtain a better understanding of the reservoir heterogeneities and fluids behavior, therefore; predict their future performance, create an optimal field development plan and maximize their productivity. During periods of Upper Cretaceous and Paleocene are observed different processes of transport and deposition in the Santos Basin, which generated large variations in the sedimentation of grains regionally, affecting directly the reservoir properties, this implies that there is a high degree of uncertainty in the regional Petrophysics properties estimation. To remove the uncertainty, is proposed to regionally evaluate the reservoir rock in the Upper Cretaceous and Paleocene by Petrophysics characterization and rock physics modeling in the southwest Santos Basin, Brazil. To do this, lithofacies logs were determined to calculate the Petrophysics properties on interest areas, finally matrix density, the compressibility and shear modules were determined through the implementation of the methods proposed by Castagna (1985), Greenberg & Castagna (1992), Xu & White (1995) and Sun (2004).